Analisis Yuridis Putusan Pemidanaan Terhadap Tindak Pidana Terorisme (Putusan Nomor 79/Pid.Sus/2020/PN.Jkt.Tim) - Herlangga, Armanda; Suarda, I Gede Widhiana; Nugroho, Fiska Maulidian (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2022)
This study examines the decision number: 79/Pid.Sus/2020/PN.Jkt.Tim in a case of criminal action of terrorism. This type of research is a normative legal research. The approaches used are the legal, case, and conseptual ones. The results showed that based on Decision Number: 79/Pid.Sus/2020/PN.Jkt.Tim found that the public prosecutor was not careful in formulating the charges, the indictment of the Public Prosecutor is not in accordance with the actions that have been carried out by the defendant as stated in the Terrorism Law. The public prosecutor does not meet the requirements in making an indictment as regulated in the provisions of Article 143 paragraph (2) of the Criminal Procedure Code regarding the formal and material requirements in making an indictment in a criminal act that is charged to the defendant. And based on the decision in Decision Number: 79/Pid.Sus/2020/PN.Jkt.Tim, the judge's consideration is not in accordance with what was done by the defendant who considered that the defendant had attempted to commit a criminal act of terrorism as stated in the facts revealed by the trial in the decision number: 79/Pid.Sus/2020/PN.Jkt.Tim.